Biopsychosocial aspects related to social isolation during the Covid-19 pandemic: an integrative review (Research, Society and Development, 2020)
The aim of this study was to learn the biopsychosocial impact of social isolation resulting from the COVID-19 pandemic. The research is an integrative literature review conducted in April 2020, using the databases of the Virtual Health Library (VHL) that included the Latin American Literature in Health Sciences (Lilacs), the Medical Literature Analysis and Retrieval System Online (Medline); the Medline Publisher (PubMed) and Scientific Electronic Library Online (SciELO) virtual libraries using the following search strategy: “coronavirus” [AND] “social isolation”, adopting the time frame from 2015 to 2020. Eight studies were analyzed. The analysis of the materials led to the classification of the topics covered in four major areas: a) studies describing the current scenario of the coronavirus pandemic; b) studies related to laws and organizational measures that were implemented in response to the pandemic; c) evaluations of the effect of measures implemented in specific territories regions within countries and; d) psychological analysis of groups affected by the social isolation resulting from COVID-19. As a conclusion, it is observed that biopsychosocial damage and decreased quality of life correlates to social isolation. Those effects include increased anxiety, stress, decreased quality of sleep, as well as the work overload of frontline professionals.